2016
DOI: 10.1371/journal.pone.0163139
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of p38, MAPK, PI3K or Rho Kinase Inhibitors on Bacterial Phagocytosis and Efferocytosis by Macrophages in COPD

Abstract: Pulmonary inflammation and bacterial colonization are central to the pathogenesis of chronic obstructive pulmonary disease (COPD). Defects in macrophage phagocytosis of both bacteria and apoptotic cells contribute to the COPD phenotype. Small molecule inhibitors with anti-inflammatory activity against p38 mitogen activated protein kinases (MAPKs), phosphatidyl-inositol-3 kinase (PI3K) and Rho kinase (ROCK) are being investigated as novel therapeutics in COPD. Concerns exist, however, about off-target effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 83 publications
2
44
0
Order By: Relevance
“…There has been a lot of interest in looking if inhibiting downstream pathways of phagocytosis can improve macrophage function in COPD as these pathways can have different effects [70] , [71] . Previous research as part of COPD MAP cohort demonstrated that inhibition of the individual subunits of PI3K or ROCK pathways did not alter phagocytosis or intracellular killing of bacteria by alveolar macrophages [72] . However ROCK inhibition reversed defective efferocytosis highlighting potential differences in pathways regulating bacterial phagocytosis versus efferocytosis [72] .…”
Section: Pharmacological Restoration Of Phagocytosismentioning
confidence: 87%
See 1 more Smart Citation
“…There has been a lot of interest in looking if inhibiting downstream pathways of phagocytosis can improve macrophage function in COPD as these pathways can have different effects [70] , [71] . Previous research as part of COPD MAP cohort demonstrated that inhibition of the individual subunits of PI3K or ROCK pathways did not alter phagocytosis or intracellular killing of bacteria by alveolar macrophages [72] . However ROCK inhibition reversed defective efferocytosis highlighting potential differences in pathways regulating bacterial phagocytosis versus efferocytosis [72] .…”
Section: Pharmacological Restoration Of Phagocytosismentioning
confidence: 87%
“…Previous research as part of COPD MAP cohort demonstrated that inhibition of the individual subunits of PI3K or ROCK pathways did not alter phagocytosis or intracellular killing of bacteria by alveolar macrophages [72] . However ROCK inhibition reversed defective efferocytosis highlighting potential differences in pathways regulating bacterial phagocytosis versus efferocytosis [72] . The team of Sandra Hodge recently also described an effect for thymoquinone on improved macrophage efferocytosis and phagocytosis in COPD [73] .…”
Section: Pharmacological Restoration Of Phagocytosismentioning
confidence: 87%
“…Although bronchodilators have been the primary treatment option for airflow limitations typical in COPD [ 24 ], they predominantly address the symptoms and not the underlying immune pathogenesis of the disease. Novel treatments target specific molecular pathways thought to be pivotal in the pathogenesis of the disease, such as small molecule inhibitors with anti-inflammatory activity against p38 mitogen-activated protein kinases, phosphatidyl-inositol-3 kinase, and Rho kinase [ 53 ].…”
Section: Therapeutic Targeting Of Macrophages In Copdmentioning
confidence: 99%
“…In another report, the expression of the macrophage scavenger receptor 1 in monocyte-derived macrophages was associated with genetic variants which also controlled in vitro cell adhesion and survival in culture [ 227 ]. Finally, conflicting data have been published concerning the involvement of p38, ERK1/2, PI3K, ROCK, and p65 kinases and cytoskeletal changes in AM phagocytosis in COPD [ 147 , 228 ].…”
Section: Ams In Copdmentioning
confidence: 99%